Sk8er Gramps - Lau, Yee Jing (Nanyang Technological University, 2023)
A comic that follows the life of a 70-year-old man, who after retirement decided to pick up skateboarding and unexpectedly found his love for the sport. This is despite the difficulties he went through due to his age and more delicate physique. We journey with him as he takes up the sport, overcomes challenges and obstacles, and forms new friendships along the way. It is aimed at readers of all ages and aims to promote active aging while highlighting the benefits of pursuing new hobbies and interests during retirement. It also seeks to break down stereotypes and challenge ageism by showcasing an elderly person engaging in an equally physically demanding and exciting activity.